Nanotech for clean water: an alternative approaches to control water pollution - Shit, Simanta; Sharma, K (Recent Research in Science and Technology, 2012)
Wastewater is any water that has been adversely contaminated by organic pollutants, bacteria and microorganisms, industrial effluent or any compound that deteriorated its initial quality. The recent advances and application of nanotechnology for waste water treatment is dealt briefly in this review. During treatment of municipal waste water it has to consider all aspect related to contamination and has to ensure that water is free from all harmful substances. Nanotechnology has new procedures for the treatment of waste water. These techniques are fabrication of membrane from nanomaterials and use of catalyst for decomposition of noxious compound in water.